Identification of High-Yielding Iron-Biofortified Open-Pollinated Varieties of Pearl Millet in West Africa - Gangashetty, Prakash I.; Riyazaddin, Mohammed; Sanogo, Moussa Daouda; Inousa, Drabo; Issoufou, Kassari Ango; Asungre, Peter A.; Sy, Ousmane; Govindaraj, Mahalingam; Ignatius, Angarawai Ijantiku (Frontiers in Plant Science, 2021)
Pearl millet is the predominant food and fodder crop in West Africa. The present study was carried out to test the newly developed high grain iron varieties and to identify the stability of these varieties for grain yield, grain iron (Fe), and zinc (Zn) contents across 10 locations in West Africa (Niger, Nigeria, Mali, Burkina Faso, Senegal, and Ghana). The test material consisted of 30 varieties including both biofortified (8) and non-biofortified (22). The trial was conducted in a randomized complete block design in three replications. Analysis of variance revealed highly significant variability for yield and micronutrient traits. The presence of G × E indicated traits expression are significantly influenced by both genetic and GxE factors, for grain Fe and Zn content. Days to flowering and plant height showed less G x E . Suggesting these traits are largely under genetic control. The genotypes CHAKTI (46 days), ICTP 8203 (46 days), ICMV 177002 (50 days), ICMV 177003 (48 days), and Moro (53 days) have exhibited early flowering across locations lead to early maturity. CHAKTI (1.42 t/ha yield; 62.24 mg/kg Fe, 47.29 mg/kg Zn) and ICMP 177002 (1.19t/ha yield, 62.62 mg/kg Fe, 46.62 mg/kg Zn) has performed well for grain yield, and micronutrients, across locations, compared to check. The AMMI analysis of variance revealed highly significant genotypic differences, the mean sum of squares of environment, and its interaction with the genotypes. Based on the AMMI stability value, the most stable genotype is SOSAT-C88 (ASV = 0.04) for grain yield and resistance to downy mildew; mean grain yield and stability rankings (YSI) revealed that the genotypes CHAKTI, SOSAT-C88, and ICMV IS 99001 were high yielding and expressed stability across regions. CHAKTI outperformed over others for grain yield (71% higher) especially with early maturing varieties in West Africa such as GB 8735, LCIC 9702, and Jirani and by Fe (16.11% higher) and Zn (7% higher) across locations, make a candidate high-iron variety to be promoted further for growing in the farmer fields in West and Central Africa. CHAKTI was officially released for commercial cultivation in West Africa in 2018.